Penerapan Undang-Undang Nomor 6 Tahun 2023 Tentang Cipta Kerja terhadap Izin Usaha Perkebunan Kelapa Sawit di Kawasan Hutan - Rifqi Muda Panjaitan; Alvi Syahrin; Robert Robert (Wajah Hukum, 2026)
The enactment of the Job Creation Law has currently sparked much controversy, especially among plantation entrepreneurs. The purpose of this study is to analyze the validity of oil palm plantation permits and the factors that hinder the implementation of Law Number 6 of 2023 concerning Job Creation. The research method used in this study is empirical, namely research that aims to examine the law in society. The results of the study state that the validity of oil palm plantation business permits that have been established within forest areas after the enactment of Law Number 6 of 2023 concerning Job Creation is threatened with no longer being valid. What factors hinder the implementation of Law Number 6 of 2023 concerning Job Creation for oil palm plantation business permits that have been established in forest areas consist of several factors, namely: legal substance factors, legal structure factors, legal culture factors. Procedures for resolving oil palm plantations that have been established and have business permits within forest areas that can be applied to resolve this problem can be achieved in two ways: non-litigation and litigation.